Determining the Optimal Time of Gastric Emptying in Cats Using Dry or Wet Food - Castro, Jorge Luiz Costa; Santalucia, Sergio; Ferreira, Ariele Aparecida; Moratelli, Clara Biange dos Santos; Castro, Verônica Souza Paiva; Oliveira, André Lacerda de Abreu; Guedes, Rogério Luizari; Albernaz, Vinícius Gonzalez Peres; Cancian, Maicol Ache; Raiser, Alceu Gaspar (Acta Scientiae Veterinariae, 2016)
Background: Pulmonary aspiration of gastric content can result in intraoperative and postoperative complications, such as regurgitation, gastro-esophageal reflux and esophagitis. There are variations among authors about the ideal period of solid and liquid fasting. Determination of the appropriate amount of food abstinence in surgical patients is important, because of the metabolic disorders that interfere in response to anesthetic protocol or surgical intervention. Thereby, this research aimed to evaluate the appropriate period of fasting for elective anesthesia and surgical procedures in cats, by analysis of gastric emptying time based on the daily energy requirement. Materials, Methods & Results: Seven cats of mixed breed, health and with an average weight of 2.857 ± 0.3780 were evaluated by gastroscopy for the presence of food and obtaining tissue samples. To evaluate the gastric emptying time, dry and moist food were offered at two different times, 8 h and 4 h before each evaluation, with an interval of seven days between each food treatment (dry and moist). There was no significant difference in all biochemical parameters evaluated (cholesterol, glucose, and lactate) in both fasting times and food types (P > 0.05). All animals underwent gastric biopsy for histological evaluation and urease test, to discard morphological changes. After 4 h it was observed dry food in all cat’s stomach, however just five cats presented food in their stomach after eight hours. In other hand all the animals, which ate moist food, did not present any gastric content after four hours and eight hours of feeding. Gastric mucosa were considered normal in all cats with moderate amount of Helicobacter sp. Discussion: The difficulty of a consensus on the fast time in cats, and the great variability of the emptying time according to the feeding type, makes this study useful as basis for future studies on fasting with wet food, as well as providing immediate clinical application in surgical routine. Only a moderate gastritis related to helicobacter sp. was detected, but even healthy animals can carry Helicobacter sp. Four h of fasting time if feed the patient with 80% humidity ration improve anesthetic security of the patient with typical biochemical values. As shown, the appropriate preoperative fasting directly implies on decrease in the number of complications related to full stomach. Thus, always should take into account the possibility to perform fast in an appropriate period to prevent vomiting and aspiration, without the risk of hypoglycemia benefiting the patient and reassuring the anesthesiologist, especially in situations requiring urgent or emergency intervention. As observed through endoscopy, even eight hours of fasting with dry feed is inappropriate due to significant gastric volume of food in almost all cats. This suggests that prolonged preoperative fasting is no guarantee of low stomach volume. Wet feed can be an option for elderly and debilitated patients requiring surgical intervention within a short period of fasting. The time varies with type and volume of food that is variable according patients and different species and digestive conditions. The research were conducted with none complications. By means, this experiment it was concluded that the fasting time of 4 h with 80% humidity moist food allows complete gastric emptying without any complication.